2022
DOI: 10.3390/antiox11112252
|View full text |Cite
|
Sign up to set email alerts
|

Association between Dietary Total Antioxidant Capacity of Antioxidant Vitamins and the Risk of Stroke among US Adults

Abstract: The intake of antioxidant vitamins can scavenge free radicals and reduce oxidative stress, which may be beneficial for stroke. However, the relationship between total antioxidant capacity (TAC) of antioxidant vitamins and stroke is controversial. This study aims to investigate the association between dietary TAC and the risk of stroke in US adults. This study included participants over 20 years old from the 2001–2018 National Health and Nutrition Examination Survey (NHANES). Data from two 24 h dietary recalls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
2
9
1
Order By: Relevance
“…CDAI is another new method used to evaluate oxidative stress and inflammation status of certain diseases. Previous studies showed that dietary total antioxidant capacity (DTAC) is negatively associated with oxidative stress of hyperuricemia, rheumatoid arthritis, hypertension, and CKD (Choi et al, 2009; Cyuńczyk et al, 2022; Moradi et al, 2022; Yang et al, 2022). These results are consistent with our findings that DTAC is associated with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…CDAI is another new method used to evaluate oxidative stress and inflammation status of certain diseases. Previous studies showed that dietary total antioxidant capacity (DTAC) is negatively associated with oxidative stress of hyperuricemia, rheumatoid arthritis, hypertension, and CKD (Choi et al, 2009; Cyuńczyk et al, 2022; Moradi et al, 2022; Yang et al, 2022). These results are consistent with our findings that DTAC is associated with oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Participants who answered "Yes" was defined as patients with stroke. The strategy to identify patients with stroke was consistent with previous studies [22][23][24]. Participants with unknown stroke status were excluded from the study.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the prevalence of stroke and cigarette use information was obtained from questionnaires. Although data from questionnaires have been widely used in clinical research [23,24], it is concerning that the questionnaire-based data might result in bias. Moreover, this study was conducted Fig.…”
Section: Discussionmentioning
confidence: 99%
“…DTAC was assessed using eight antioxidative vitamins: vitamin A, vitamin C, vitamin E, α‐carotene, β‐cryptoxanthin, β‐carotene, lutein‐zeaxanthin and lycopene (Yang et al, 2022). The DTAC database of US diets, developed by Floegel et al, provided reference values for vitamin C‐equivalent antioxidant capacity, encompassing all eight antioxidant vitamins (Floegel et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, nutrients are not consumed in isolation, and the synergistic effects of multiple components can have a combined impact (Hu, 2002; Jacobs et al, 2009). Several diet‐related indices, such as dietary oxidative balance score (DOBS), dietary total antioxidant capacity (DTAC) of antioxidant vitamins and composite dietary antioxidant index (CDAI), have been developed to assess dietary antioxidant intake (Maugeri et al, 2019; Wright et al, 2004; Yang et al, 2022; Zhang et al, 2022). Thus, the significance of dietary antioxidant intake in preventing periodontitis warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%